2013
DOI: 10.1177/1010539511420703
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypertension in a population-based sample of postmenopausal women in Kolkata, West Bengal, India

Abstract: Hypertension is a major public health problem worldwide. However, limited information is available regarding the risk factors for hypertension in postmenopausal women, particularly in urban populations in developing countries such as India. To investigate whether adiposity measures, serum lipids and lipoproteins as well as fasting plasma glucose can predict the risk of hypertension in a population based sample of postmenopausal women in Kolkata, India, we conducted a cross-sectional study of 415 postmenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Similar findings have been reported by several workers. [15][16][17] Contrary to this several workers reported a higher prevalence of hypertension. [17][18][19][20][21][22][23] Lower prevalence of hypertension has been observed by some researchers.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Similar findings have been reported by several workers. [15][16][17] Contrary to this several workers reported a higher prevalence of hypertension. [17][18][19][20][21][22][23] Lower prevalence of hypertension has been observed by some researchers.…”
Section: Discussionmentioning
confidence: 41%
“…[15][16][17] Contrary to this several workers reported a higher prevalence of hypertension. [17][18][19][20][21][22][23] Lower prevalence of hypertension has been observed by some researchers. [24][25][26][27] The result of the present study shows an increase in prevalence of hypertension with an increase in age.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The mean difference in DBP change from baseline between the DSS and CBS at the 12th month, adjusted for age, gender, height, waist, BMI, alcohol intake, pickle and papad intake, and portions of vegetable/fruit consumed per day between both the groups was −2.83 mm Hg (95% CI: −5.78 to 0.13 mm Hg; P =0.083). The chosen variables to adjust for differences between the 2 groups were based on the baseline data differences between CBS and DSS groups, systematic literature review performed by our group, and other articles (from India) that reported on the associations between the covariate(s) and HTN . Table and Figure show the unadjusted and adjusted mean difference in SBP and DBP change from baseline between DSS and CBS groups at 6 and 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…These studies indicate that ApoA1 and ApoB might have key effects on managing blood pressure and the HTN pathological process. Previous studies found lower levels of lipoprotein, ApoA and ApoB in Chinese adults than in whites [26]; however, little data are available for Chinese adults [20,27], who differ from their Western counterparts in lipid levels [21][22][23][24][25]. Also, the different prevalence rates of obesity between Western and Chinese populations [28] might influence the Apo-HTN association because body fat affects blood pressure [29].…”
Section: Introductionmentioning
confidence: 99%